Effects of probiotics on serum biochemical parameters in rats (Bangladesh Veterinarian, 2012)
Twelve one-month-old rats (Rattus norvegicus) were randomly divided into three groups of four. All groups were fed commercial diet, 20 g/rat for seven days. In addition, groups A and B were given home made probiotic (curd), commercial probiotic (Bio-Top®). Total serum cholesterol in A, B and C was 91.6 ± 3.6, 92.1 ± 1.2 mg, 122.3 ± 4.9 mg/dl, respectively. Triglyceride in A (47.5 ± 16.4 mg/dl), B (44.0 ± 5.0 mg/dl) and C (146.4 ± 25.4 mg/dl) differed significantly (P